The balcony - e (New York : Simon & Schuster Books for Young Readers, an imprint of Simon & Schuster Children's Publishing Division, 2019)
When a little girl moves from her home to an apartment in the city, she takes her plants with her and one by one they grow and bloom and change both her world and the world all around her as she makes a new friend.
"A Paula Wiseman Book."